FROM FORMATION TO REDEFINITION: EXPLORING THE PRINCIPLES OF CONSTITUENT UNIT BOUNDARY (UN)MAKING IN THE ETHIOPIAN FEDERATION - Bekele (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2024)
This article examined the principles underlied the (un)making of constituent unit boundaries of the Ethiopian federation from its inception in 1992 until its redefinition in 1994. It organized the data using various media reports, retrieved life experiences from seven purposely chosen Key Informant Interviews, and conducted a qualitative analysis of documents. Accordingly, it revealed eight (8) principles that were utilized in the establishment of interregional states’ boundaries in Ethiopia, including the “four principles” enshrined in the 1995 Federal Democratic Republic of Ethiopia (FDRE) Constitution and the principles of agreement among and/or between adjacent nationalities, ethnoterritoriality, ethnoculturality, and ethnolinguisticity. It also revealed historical considerations and informal agreements between officials. It was discovered that the political objectives of ethno-national groupings dictated the implementation of these principles. It is discovered that interregional state boundaries making of the 1992 had a paramount ramifications for nationality groups’ ability to safeguard, promote, and preserve the ethnonational groups’ identities.